WORK-LIFE BALANCE, BURNOUT, DAN WORK ENGAGEMENT PADA PERAWAT - Rizqi Zulfa Qatrunnada; Arifah Wafiq Azizah; Alivia Putri Zahra (Jurnal Ilmiah Psikologi Candrajiwa, 2025)
This study aimed to determine the relationship between work-life balance, burnout, and work engagement among nurses. This research was conducted at X Academic Hospital located in Surakarta. The respondents were nurses who had more than one year of employment and held permanent employee status. This study employed a non-probability sampling method, utilizing a purposive sampling technique, and collected data using Google Forms. A total of 76 nurses who were willing to participate and met the inclusion criteria took part in this study. The measuring instruments used were the 9-item version of the Utrecht Work Engagement Scale (UWES-9), the Maslach Burnout Inventory (MBI), and the Work-Life Balance Scale. The analysis results showed that there was a positive and significant relationship between work-life balance and work engagement (r = 0.466, p < .001), a negative and significant relationship between burnout and work engagement (r = -0.231, p = .045), and a negative and significant relationship between work-life balance and burnout among nurses (r = -0.587, p < .001). The research findings concluded that a high work-life balance correlated with low burnout and increased work engagement among nurses. This research suggests the need to enhance both the personal aspects of nurses and organizational interventions to promote a healthier work environment for nurses.